Sheep Herd Health Practices with Focus on Lamb Health – a Study among Sheep Farmers in the Highlands of Ethiopia - Prevalent sheep herd health practices among smallholder sheep farmers in the highlands of Ethiopia - Genfors, Elisabeth; Båge, Renée; Magnusson, Ulf; Wieland, Barbara; Animal and Human Health, International Livestock Research Institute (Swedish University of Agricultural Sciences, 2023)
Preventive health care and healthcare routines are practiced to prevent disease and possible subsequent death in animals, regardless of species at topic. To potentiate young stock health and survival, preventive health care measures should be applied already at time of mating, and continuously be implemented during pregnancy, delivery and throughout the first living months of the offspring.

Lamb mortality in Ethiopia have repeatedly been observed to be high. This study thus aims to investigate the relationship between prevalent routines and occurrence of lamb mortality in concerned herds. The study group is Ethiopian smallholder sheep farmers, and the data was collected in personal interviews strictly following an ad-hoc created questionnaire. The data aimed to qualitatively describe and document existing routines and prerequisites throughout previous year.

The dataset consists of one data file (6227 rows × 124 columns) with questionnaire answers. For more information about questionnaire and variable names, see documentation files. The document files consist of a few pages with classifications and explanations of the data set. The files also incorporate the questionnaire from which the data is collected, as well as a document explaining the answers given in the interviews.

The questionnaire was developed to evaluate commonly prevalent sheep herd health practices. It was developed by experts on the subject, with support in relevant literature. It was developed for this data collection solely.

Förebyggande djurhälsovård och djurhälsovårdsrutiner utförs för att förebygga sjukdom och eventuell påföljande död hos djur, oavsett vilken art det rör. För att förbättra hälsostatus och överlevnad hos unga djur bör förebyggande hälsoåtgärder sättas in redan vid betäckning av modern, och sedan fortgå under hennes dräktighet, förlossning samt under de första månaderna av den unga individens liv.

Lammdödlighet i Etiopien har vid upprepade observationer rapporterats vara hög. Den här studien ämnar att utreda relationen mellan befintliga djurhälsovårdsrutiner och förekomst av lammdödlighet i berörda flockar. Studiepopulationen bestod av Etiopiska småbrukande fårbönder, och datan samlades in via personliga intervjuer som strikt följde ett för ändamålet utformat frågeformulär. Målet med datan är att på ett kvalitativt sätt beskriva och dokumentera förekommande rutiner och förutsättningar som bönderna haft under det gångna året.

Datasetet består av en datafil (6227 rader × 124 kolumner) med enkätsvar. För mer information om enkät och ingående variabler, se dokumentationsfiler. Dokumentationsfilerna innehåller beskrivningar av datasetet, men även det frågeformulär som intervjuerna baserades på samt ett dokument som ger ytterligare fördjupad förklaring till en del datatermer i datasetet.

Frågeformuläret är utformat för att samla in data om vanligt förekommande fårhälsorutiner. Det togs fram av inom ämnet kunniga personer, med stöd från relevant litteratur, specifikt för denna datainsamling.
Hantering och rutiner av fårflocken med fokus på lammhälsa – en studie bland fårbönder i Etiopiska höglandet - Förekommande hälsorutiner i fårflockar bland småbrukande fårbönder i Etiopiska höglandet
Keywords: Preventive Medicine; Förebyggande medicin; Sheep; Får; Survival Rate; Överlevnadsfrekvens; Reproductive Health; Fortplantningshälsa; Lamb health; Lammhälsa; Preventive animal healthcare; Förebyggande djurhälsovård; Veterinary Science; Veterinärmedicin